TELEDENTISTRY IN A JURIDICAL PERSPECTIVE: CRIMINAL, CIVIL AND ADMINISTRATIVE ASPECTS - Nyoman Ayu Anggayanti; Ida Bagus Fajar Manuaba; I Gusti Agung Gede Utara Hartawan (Interdental Jurnal Kedokteran Gigi (IJKG), 2023)
Introduction: To address the limitations resulting from the implementation of health protocols in providing healthcare services to patients, a solution was found in the utilization of information and communication technology to support healthcare services for patients in the form of telehealth, often known as telemedicine. Review: According to Article 1, Paragraph 21 of Law Number 17 of 2023 regarding Health, telemedicine is defined as the provision and facilitation of healthcare services, including public health, health information services, and self-care services, through telecommunications and digital communication technology. One of the aspects of telemedicine in the field of dentistry is teledentistry, which can be a solution for optimizing dental and oral healthcare services for individuals and the community. However, there are various issues in its implementation, especially related to legal issues such as licensing, patient electronic medical record privacy and confidentiality, clinical guidelines, and others that are highly vulnerable to data discrepancies, falsification, or digital patient data leakage. Conclusion: These issues can potentially lead to medical disputes that may enter the legal realm. On the other hand, teledentistry services also play a crucial role in improving public health, especially in dental and oral health in Indonesia, particularly during the COVID-19 pandemic. Therefore, the development of teledentistry services needs to be continuously improved, both in terms of systems and regulations, to provide security and legal certainty for the Indonesian population.